Family Associations as Social Capital for Families and Society - Carrà, Elisabetta (Socialinė teorija, empirija, politika ir praktika, 2017)
At a time of renewed interest in the family, family associations are attracting increasing attention. This is due to a growing awareness that fraying social bonds and the general crisis of the welfare system are related to lack of support for the family and its code of solidarity. This article explores a number of issues, starting with the question of the identity of a family association, both in theory, within the framework of relational sociology and international literature, and in practice, in light of the international federations of family associations’ membership criteria. Finally, family associations will be described according with the concept of social capital, to show that when families form associations with other families they become an irreplaceable resource for society.